Enterogastric brake in rats with segmental bowel resection: Role of capsaicin-sensitive nerves - YEGEN, BERRAK; GÜLPINAR, MEHMET ALİ; YEGEN, ŞEVKET CUMHUR (WILEY, 2002)
1. Unabsorbed nutrients in the distal gut inhibit upper gastrointestinal motility. 2. The aim of the present study was to investigate changes in gastric motility following segmental resections and to evaluate the role of capsaicin-sensitive afferent neurons that may be responsible for these changes. 3. Wistar albino rats of both sexes (200-250 g) were used. Under aseptic conditions and anaesthesia (100 mg/kg ketamine), a baby-feeding tube was placed distal to the resection in either the ileum or caecum for intraluminal perfusion of saline or 20% lipid. In one group of rats, capsaicin was perfused (0.6%) for afferent denervation. One group of rats underwent jejunal and ileal resections with end-to-end anastomosis of the remaining segments and were cannulated distal to these anastomosis. Ten days after the surgery, the percentage gastric emptying of a solid meal was calculated. 4. Intra-ileal (18%) and intracaecal (34%) lipid perfusions delayed gastric emptying compared with groups perfused with saline (54% and 74%, respectively; P < 0.001 and P < 0.01). The delay in gastric emptying by ileal perfusion was significantly greater than that following caecal perfusion (P < 0.05). With both resections, gastric emptying was delayed compared with sham groups (P < 0.05-0.01). Local administration of capsaicin abolished the inhibitory effect of lipid on gastric emptying in healthy intact rats and in the jejunal-resection group, whereas a partial reversal was seen in the ileal-resection group. 5. In conclusion, the present data demonstrate that in both healthy intact rat groups and in short bowel groups, capsaicin-sensitive extrinsic neurons participate in 'brake' mechanisms of the distal gut.
Keywords: capsaicin; enterogastric brake; gastric emptying; intestinal resection; short bowel; PEPTIDE-YY; ILEAL BRAKE; COLONIC BRAKE; INTESTINAL TRANSIT; JEJUNAL MOTILITY; FAT; RELEASE; GUT; ENTEROGLUCAGON; INHIBITION